Molecular analysis and genetic diversity of Aedes albopictus (Diptera, Culicidae) from China. (19th May 2018) - Ruiling, Zhang; Peien, Leng; Xuejun, Wang; Zhong, Zhang
Abstract: Aedes albopictus is one of the most invasive species, which can carry Dengue virus, Yellow fever virus and more than twenty arboviruses. Based on mitochondrial gene cytochrome c oxidase I (COI) and samples collected from 17 populations, we investigated the molecular character and genetic diversity of Ae. albopictus from China. Altogether, 25 haplotypes were detected, including 10 shared haplotypes and 15 private haplotypes. H1 was the dominant haplotype, which is widely distributed in 13 populations. Tajima' D value of most populations was significantly negative, demonstrating that populations experienced rapid range expansion recently. Most haplotypes clustered together both in phylogenetic and median-joining network analysis without clear phylogeographic patterns. However, neutrality tests revealed shallow divergences among Hainan and Guangxi with other populations (0.15599 ≤ FST ≤ 0.75858), which probably due to interrupted gene flow, caused by geographical isolations. In conclusion, Ae. albopictus populations showed low genetic diversity in China.